2017
DOI: 10.1016/j.rmcr.2017.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary cryptococcosis in a ruxolitinib-treated patient with primary myelofibrosis

Abstract: We present the case of a 79-year-old man who showed multiple pulmonary nodules on chest computed tomography (CT) after being treated for 6 months with ruxolitinib, an inhibitor of Janus kinase (JAK) 1 and 2, to treat primary myelofibrosis. We examined the lesions by bronchoscopy, and the biopsy specimen revealed fungus bodies of Cryptococcus with granulomatous inflammation. As a result, the patient was diagnosed with pulmonary cryptococcosis. The patient was treated with fluconazole (200 mg daily for 2 weeks) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Eight papers were excluded for the following reasons: pooled analysis ( n = 1), follow‐up of phase I or II trial ( n = 1), sub‐analyses ( n = 2), data on extension phase study with a shorter follow‐up ( n = 2), redundant publications ( n = 2). Five phase III RCTs (3 phase IIIa with their most recently published extended phase (750 patients) and 2 phase IIIb RCTs (283 patients)), 6 phase IV studies (1524 patients) and 28 case report publications (31 patients, of whom 4 were included also in phase III studies and 1 in phase IV study) were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Eight papers were excluded for the following reasons: pooled analysis ( n = 1), follow‐up of phase I or II trial ( n = 1), sub‐analyses ( n = 2), data on extension phase study with a shorter follow‐up ( n = 2), redundant publications ( n = 2). Five phase III RCTs (3 phase IIIa with their most recently published extended phase (750 patients) and 2 phase IIIb RCTs (283 patients)), 6 phase IV studies (1524 patients) and 28 case report publications (31 patients, of whom 4 were included also in phase III studies and 1 in phase IV study) were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…This case draws attention to three key factors. The first is the degree of immunosuppression seen with ruxolitinib and the increasing number of reported fungal cases associated with the drug [58]. The second, which was noted on initial phase III trials of ruxolitinib, but must be emphasized, is that the adverse effects from immunosuppression may occur at various intervals after the initiation of ruxolitinib.…”
Section: Discussionmentioning
confidence: 99%
“…The phase 3 study of ruxolitinib (COMFORT II trial) [4] reported that reactivation of herpes zoster virus and tuberculosis were the predominant infections seen with ruxolitinib, as well as a trend towards higher rates of bacterial infections. Since that time, case reports have emerged, documenting the development of Pneumocystis jiroveci pneumonitis, toxoplasmosis retinitis, progressive multifocal leukoencephalopathy (PML), as well as cryptococcal meningoencephalitis and pulmonary cryptococcus in patients treated with ruxolitinib [59].…”
Section: Introductionmentioning
confidence: 99%
“…neoformans [ 16 , 17 , 19 22 , 26 ]. To date, myelofibrosis treatment of two patients with Ruxolitinib, which inhibits JAK1,2 and likely STAT1, is hypothesized to have contributed to the development of cryptococcosis in these individuals [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%